Treatment of Convulsive Status Epilepticus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Definition, etiology, treatment, and outcome of convulsive status epilepticus in children and adults are outlined by a group of experts and sponsored by the Epilepsy Foundation of America.